2017
DOI: 10.3390/ijerph14060664
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness, Physical Activity, Sedentary Behavior, or Diet—What Are the Correlates of Obesity in Polish School Children?

Abstract: There is substantial evidence of rising prevalence of overweight and obesity and its co-morbidities among children in western-high income developed countries. In the European Union, the prevalence of overweight and obesity is increasing fastest among Polish children. Yet, there is paucity of evidence on the relationship of behavioral factors with body weight status of children in Poland. This study examined the association of obesity with physical fitness, physical activity, sedentary behavior and diet among P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
(47 reference statements)
3
15
1
1
Order By: Relevance
“…Las correlaciones encontradas en el presente estudio muestran que existe una correlación negativa entre la AF y los indicadores de obesidad (IMC y CC), al mostrar que los niños que reportan menos AF, son los que presentan mayor obesidad. Resultados similares se encontraron en un estudio hecho por Czyż et al 21 en escolares de Polonia, en donde las correlaciones negativas entre el VO 2 max e indicadores antropométricos como el porcentaje de grasa corporal (%GC) y el IMC reflejan que los escolares que realizan menos AF o que presentan menos VO 2 max, son los que presentan mayor %GC y mayor IMC.…”
Section: Discussionunclassified
“…Las correlaciones encontradas en el presente estudio muestran que existe una correlación negativa entre la AF y los indicadores de obesidad (IMC y CC), al mostrar que los niños que reportan menos AF, son los que presentan mayor obesidad. Resultados similares se encontraron en un estudio hecho por Czyż et al 21 en escolares de Polonia, en donde las correlaciones negativas entre el VO 2 max e indicadores antropométricos como el porcentaje de grasa corporal (%GC) y el IMC reflejan que los escolares que realizan menos AF o que presentan menos VO 2 max, son los que presentan mayor %GC y mayor IMC.…”
Section: Discussionunclassified
“…As seen towards the urban, educated and economically stable community, adolescents are found to be at a similar risk as reported in the studies from high income countries. 22,23 Adolescent obesity in India is seen to be reported in the range of 3.6% to 8.06% by various studies. 18,[24][25][26] Study by Jain et al, reported prevalence of obesity 8.06% while, another study from Odisha reported 3.68%.…”
Section: Obesity Totalmentioning
confidence: 99%
“…Recently, body mass gain in various age populations, including children and adolescents, has been noticeable ( Czyż et al, 2017 ; Brzeziński et al, 2018 ). This problem is classified as the major public health challenge of the 21st century ( Nittari et al, 2019 ; Spinelli et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…This problem is classified as the major public health challenge of the 21st century ( Nittari et al, 2019 ; Spinelli et al, 2019 ). Currently, over 43 million children in the world are overweight or obese ( Güngör, 2014 ; Czyż et al, 2017 ). According to a World Health Organization report, every third child in European Union countries is overweight, and every fifth child in Poland suffers from overweight or obesity ( Nittari et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%